EVALUATION OF THE POSSIBILITIES OF INCREASING OIL YIELD IN HIGH-VISCOSITY OIL FIELDS USING THERMAL METHODS - Bobomurodov Utkir Ziyadullayevich; Sultonov Nodir Normuradovich (American Journals Publishing, 2023)
The problem of increasing the level of oil extraction from the used fields or, in the expression of oilmen, increasing the final oil yield of the formations, has become one of the most important economic tasks in recent years. The economic development plans of each oil-receiving country envisage the full use of oil reserves, increasing the oil yield of layers, and in this direction, the implementation of new methods on a scientific-research, testing and industrial scale.